Effect of Early Initiation on Exclusive Breastfeeding in Blindungan Village Blindungan District Bondowoso - susilowati susilowati; Damon Wicaksi (D'Nursing and Health Journal (DNHJ), 2021)
Introduction: Mothers who do not provide exclusive and customary breastfeeding to their babies are influenced by several factors such as insufficient breast milk so that the babies often fuss and cry. Exclusive breastfeeding constraints are also due to the provision of food and drinks to the baby before breastfeeding, such as honey and formula milk, and the distrust of mothers in breastfeeding the baby. Method: The research method used is observational analytic with cross sectional approach to see the effect of independent variables on the dependent variable. Result: The results of this study were 69 respondents who did Early Initiation of Breastfeeding (IMD), 23 respondents (33.3%) succeeded in giving exclusive breastfeeding, and 18 respondents (26.1%) were unable to provide exclusive breastfeeding. Mothers who did not perform IMD and were able to provide exclusive breastfeeding were 6 respondents (8.7%) and 22 respondents (31.9%) were unable to exclusively breastfeed. This shows that IMD can increase exclusive breastfeeding, while mothers who do not do IMD are at risk of not being able to provide exclusive breastfeeding. Conclusion: From the results of this study, it is necessary to increase health education about improving the quality of mothers in carrying out IMD and exclusive breastfeeding.